WhatsApp e desordem informacional nas eleições de 2022 : uma vartografia das controvérsias sobre a atuação do poder judiciário e a desconfiança sobre o processo eleitoral durante o 2º turno das eleições presidenciais - Aline Margotti de Carvalho (2023)
This research investigates the informational disorder in the 2022 Brazil elections. We propose an examination of the controversy surrounding the role of higher instances of the judiciary and the distrust in the electoral process during the second round of the presidential elections in 2022. We analyze the most shared contents and messages in the groups monitored by the WhatsApp Monitor tool. The research maps the argumentative positions, identifying, through the methodology of the Cartography of Controversies, the connected and structured arguments in the discourses, and the worldviews present in the analyzed contents. To perform the analysis, we start from the conceptualization of truth, post-truth, epistemic crisis, platforms, and informational disorder. We use Actor-Network Theory as the conceptual-methodological basis for the Cartography of Controversies, in addition to the use of content analysis and Greimasian semiotics. The results highlight the use of camouflage strategies to confer veracity to the shared contents and the predominance of certain sub-controversies. We observe the interconnection between discussions on WhatsApp and the offline environment, emphasizing the need for multidisciplinary approaches to understanding informational disorder.